Farmer selection of sources of information for nitrogen management in the US Midwest: Implications for environmental programs. (January 2018) - Stuart, D.; Denny, R.C.H.; Houser, M.; Reimer, A.P.; Marquart-Pyatt, S.
Abstract: Nitrogen fertilizer has increased crop yields, but in many regions inefficient use has also resulted in water pollution and greenhouse gas emissions. Attempts to address these environmental issues focus on education and the adoption of more efficient practices. To understand why inefficient use of nitrogen fertilizer persists, scholars have examined factors influencing management decisions including sources of information. Drawing from personal interviews and a mail survey of corn farmers in the Midwest region of the United States, this study goes beyond research that identifies what sources of information are important and examines how different sources are weighed and combined, why some sources are more influential than others, and what organizations and individuals farmers trust given the many private and public sources of information available. We find that most farmers combine several different sources of information to guide their nitrogen fertilizer decisions, private sector sources are highly influential, and that seed and fertilizer suppliers have successfully established trust with farmers through individual relationships with salespeople and crop consultants. These findings suggest that education programs to address environmental degradation associated with nitrogen fertilizer may be more successful if they involve input suppliers.